Maju Mundur Transformasi Aturan Mengenai Analisis Mengenai Dampak Lingkungan Hidup di Indonesia - Wagner, Ivan; Pratama, Erwin Aditya (Universitas Pancasakti Tegal, 2020)
Law Number 11 of 2020 concerning Job Creation has been legally enacted. The government claims that Law Job Creation is to improve the investment climate, especially in the global conditions that are being hit by the Covid-19 pandemic and are predicted to have a correlation with job creation for the peoples. However, from the time the law was proposed, discussed, endorsed, until it was signed, this law has resulted in problems, one of which is about Environmental Impact Assessment (EIA). The research questions formulated are: First, what is the historical trail of the birth and development of the EIA instrument? Second, based on the historical traces of its birth and development, is Law Job Creation a forward movement or is it a backward movement on the discourse of environmental protection? By focusing on the legal history side of EIA, using a socio-legal approach method, it can be conveyed that the traces of regulation on EIA from global discourse to national regulations are actually capable of capturing a value-based transformative vision of environmental awareness and justice. However, the transformation process was mostly carried out by the interests of foreign funding institutions that carried a vision of economic interests that reduced a value-based transformative vision. Law Job Creation is the next milestone in the transformation of regulations regarding EIA and environmental permits. If the vision for the transformation of environmental regulations is about a value-based vision towards a more environmentally aware and environment justice, it is clear that Law Job Creation is like bringing back to the starting point again.